EFFECT OF DIFFERENCE IN RADIATION OF RED LED ON TIGER BARB (Puntiustetrazona)COLOR QUALITY - Maharany Puspita Sari; Usman M Tang; Rusliadi Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRAKThis research was conducted from July to September 2018, at the Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine, University of Riau. The research aims to determinethe effect of differencesaboutduration of radiation of red LED on the color quality of Tiger Barb.This study used anexperimental method with a Completely Randomized Design (CRD) of one factor with 5treatment levels and 3 replications.The duration of radiation of red LED as a treatment is: 8 hours, 10 hours, 12 hours, 14 hours and 16 hours. The size of fish was used is 3,5–4,5 cm with 6 fishes of stocking density each aquarium. Aquarium used size (40×30×30) cm3. The fish were reared for 40 days, given blood worm, two times day of feeding frequency. Parameters observed included quality of fish color, daily growth rate, survival rate and water quality. The results showedthe difference in the duration of radiation of a red LEDhad a significantly effect on changesthe color quality of the Tiger Barb. The best treatment is ata 14 hours radiationperiode withan average color quality improvement value14,18 in theToca Colour Finder. The best growth rate is 0,46% and survival rate is100%. Keywords : Fotoperiod; Color; Tiger Barb; Puntius tetrazona